PENETAPAN DAN PENCATATAN PERKAWINAN BEDA AGAMA DI INDONESIA YANG BERKEADILAN DAN BERKEMANUSIAN - Kadek Wiwik Indrayanti (Jurnal Cakrawala Hukum, 2016)
The rights of citizens who carry out the marriage of different religions in Indonesia have not been fully protected because Law No. 1 of 1974 on Marriage has not been explicitly regulated. While the data show couples who make marriages of different religions continue to increase. This writing aims to analyze the marriage of different religions from the perspective of human rights and the solution that must be done by the state apparatus to give recognition and protection to the right of marriage partner of a different religion to embrace religion and right to form a family. The results show that the values contained within Pancasila and the 1945 Constitution provide clear protection that the right to embrace religion and the right to form a family is a recognized and protected natural right. The solution that can be done is the legal apparatus should improve its understanding of the legislation, theories, and principles of law and human rights values contained in Pancasila and the 1945 Constitution.